Integrating gender into small-scale irrigation - Lefore, Nicole; Bryan, Elizabeth; Ringler, Claudia; Meinzen-Dick, Ruth S.; Theis, Sophie (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Small-Scale Irrigation (SSI) interventions, like other development interventions, need to take into account men’s and women’s context-specific roles in agriculture and their related gender-based preferences and challenges. Understanding gender differences related to SSI technologies can help us improve targeting and better anticipate and monitor the impact of technologies on different people. Gender analysis is relevant to any SSI program, whether it seeks to avoid harm to women, to serve both men and women, or to advance women’s empowerment.